The archaeology of Native North America - Snow, Dean R., 1940- author.
1 online resource
Keywords: "The Archaeology of Native North America presents the ideas, evidence, and debates regarding the initial peopling of the continent by mobile bands of hunters and gatherers and the cultural evolution of their many lines of descent over the ensuing millennia. The emergence of farming, urban centers, and complex political organization paralleled similar developments in other world areas. With the arrival of Europeans to North America and the inevitable clashes of culture, colonizers and colonists were forever changed, also represented in the archaeological heritage of the continent. Unlike others, this book includes Mesoamerica and the Caribbean thus addressing broad regional interactions and the circulation of people, things, and ideas. This edition incorporates results of new archaeological research since publication of the first edition a decade earlier. Fifty-four new box features highlight selected archaeological sites, which are publicly accessible gateways into the study of North American archaeology. The features were authored by specialists with direct knowledge of the sites and their broad importance. Glossaries are provided at the end of every chapter to clarify specialized terminology. The book is directed to upper-level undergraduate and graduate students taking survey courses in American archaeology, as well as other advanced readers. It is extensively illustrated and includes citations to sources with their own robust bibliographies leading diligent readers deeper into the professional literature. The Archaeology of Native North America is the ideal text for courses in North American archaeology"--